Providing wireless coverage in massively crowded events using UAVs - Sawalmeh A.; Othman N.S.; Shakhatreh H.; Khreishah A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Antennas; Base stations; Unmanned aerial vehicles (UAV); Cellular network; Ground paths; Indoor path loss; Innovative solutions; k-Means algorithm; PSO algorithms; Search Algorithms; Wireless coverage; Particle swarm optimization (PSO)